Trust building behaviour within the Balinese fresh produce industry - Batt, Peter; Parining, N. (Curtin University of Technology, 2002)
Regression analysis confirms that relational satisfaction communication and the availability of alternatives have a significant positive relationship on the development of trust between vegetable farmers and traders in Bali. While no relationship between power/dependence and a strong personal relationship was found to influence trust, themaking of relational investments by traders had a significant negative relationship on trust, suggesting that such investments provide farmers with few tangible benefits.